Analysis of Students' Conceptual Understanding of Logarithm Application Problems Based on Self-Efficacy - Muzaini, Muhammad; Nasrun, Nasrun (UNNES JOURNAL, 2024)
Understanding the concept of logarithms is an essential perspective of self-efficacy gaps, as it influences students' problem-solving confidence and willingness to learn. This research utilizes a descriptive-qualitative approach to describe the differences in understanding mathematical concepts as viewed through students' self-efficacy. The research strategy employs a case study approach, where the observed phenomenon is the understanding of mathematical concepts. The research subjects consist of third-grade middle school students selected based on self-efficacy instrument results, focusing on students with high and moderate levels of self-efficacy. Data collection involves self-efficacy questionnaires, tasks on understanding mathematical concepts, interviews, and documentation. Data analysis follows the approach described by Miles et al. (2018), including data reduction, data presentation, and data verification to conclude. Research findings indicate that students who have a high level of self-efficacy are generally more adept at restating ideas, categorizing objects in difficulties, expressing ideas mathematically, and selecting the best course of action to solve issues. Furthermore, the implication suggests that fostering students' self-efficacy is crucial for enhancing their learning experience in mathematics, particularly in topics like logarithms and their applications. By recognizing the significant influence of self-efficacy on mathematical learning, educators can tailor teaching strategies to boost students' confidence and problem-solving abilities in these areas. Additionally, monitoring students' self-efficacy growth over time enables educators to adapt instructional methods effectively, ensuring that students are adequately supported in their mathematical journey. Ultimately, prioritizing the development of students' self-efficacy contributes to creating a more conducive learning environment where students feel empowered and motivated to engage with mathematical concepts and challenges. Memahami konsep logaritma merupakan perspektif penting dari kesenjangan efikasi diri, karena mempengaruhi kepercayaan diri siswa dalam memecahkan masalah dan kemauan untuk belajar. Penelitian ini menggunakan pendekatan deskriptif-kualitatif untuk mendeskripsikan perbedaan pemahaman konsep matematika dilihat melalui self-eficacy siswa. Strategi penelitian menggunakan pendekatan studi kasus, dimana fenomena yang diamati adalah pemahaman konsep matematika. Subyek penelitian terdiri dari siswa kelas III SMP yang dipilih berdasarkan hasil instrumen self efikasi, dengan fokus pada siswa yang memiliki tingkat efikasi diri tinggi dan sedang. Pengumpulan data meliputi angket efikasi diri, tugas pemahaman konsep matematika, wawancara, dan dokumentasi. Analisis data mengikuti pendekatan yang dijelaskan oleh Miles et al. (2018), meliputi reduksi data, penyajian data, dan verifikasi data untuk menyimpulkan. Temuan penelitian menunjukkan bahwa siswa yang memiliki tingkat efikasi diri yang tinggi umumnya lebih mahir dalam menyatakan kembali ide, mengkategorikan objek yang mengalami kesulitan, mengungkapkan ide secara matematis, dan memilih tindakan terbaik untuk memecahkan masalah. Hal ini menunjukkan bagaimana pembelajaran tentang logaritma dan menyelesaikan masalah penerapan logaritma dipengaruhi secara signifikan oleh efikasi diri siswa. Kesimpulan penelitian ini menyiratkan bahwa efikasi diri penting untuk proses pembelajaran matematika. Oleh karena itu, melacak pertumbuhan efikasi diri siswa dan menyesuaikannya dengan pendekatan pengajaran yang dipilih sangatlah penting.